An Argument for Small Class Size. - Mead, George C.; Kempner, Jack J. (The Accounting Review, 1970)
Reports in recent years have cited very satisfactory results achieved by scheduling large sections of elementary accounting classes. Increasing enrollments coupled with a shortage of qualified accounting professors have forced many institutions to experiment with large sections. The techniques used have run the gamut from dosed circuit television to large lecture or small quiz section combinations. One advantage of the large class approach is evident that it is economical, given scarce resources. Furthermore, consolidation of students in this manner exposes them to the presumably better teachers while graduate assistants are available to handle the laboratory or quiz sections, which apparently call for less pedagogic skill. Based upon the optimistic reports from other institutions, the article used such a system at the Missoula, Montana based-University of Montana by restructuring elementary accounting classes. However, results of a similar experiment did not succeed. The failure of the lecture and quiz section combination could be attributed to two factors including refusal of students to take the large lectures seriously and lack of time in the two-hour quiz sections to cover the assigned material adequately.